FACTORS AFFECTING THE QUALITY OF REGIONAL FINANCIAL INFORMATION IN THE PIDIE ACEH REGENCY GOVERNMENT - Cut Yunina Eriva; Ardian; Meutia Handayani; Mislinawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract